Pengaruh Rasio Asam Sitrat dan 4-carboxy-3-chlorobenzene boronic acid terhadap Quantum Yield dari Graphene Quantum Dots - Permadi, Adi; Putri, Mutiara Wilson (Journal of Industrial Process and Chemical Engineering (JOICHE), 2024)
This study investigates the effect of citric acid (CA) and 4-carboxyl-3-chlorobenzeneboronic acid (CBBA) ratio on the Quantum Yield (QY) of Graphene Quantum Dots (GQDs). The hydrothermal synthesis method was employed with various CA/CBBA molar ratios, and the optical properties were analyzed using UV-Vis and photoluminescence (PL) spectroscopy. The results show that increasing the CBBA ratio enhances fluorescence efficiency, with the highest QY of 5.075% obtained at a 1:5 ratio. The addition of CBBA improves surface passivation and reduces non-radiative recombination sites, thereby optimizing the photoluminescence properties. Furthermore, precursor ratio variation influences particle size and functional groups, affecting the solubility and stability of GQDs. These findings highlight the role of CBBA in controlling exciton recombination, making GQDs more efficient for optoelectronic, bioimaging, and biomedical applications. Further studies are needed to explore the long-term effects of CBBA doping on fluorescence stability